IRF4 and STAT3 activities are associated with the imbalanced differentiation of T-cells in responses to inhalable particulate matters - Wu, Jinzhun; Ge, Dandan; Zhong, Taoling; Chen, Zuojia; Zhou, Ying; Hou, Lingyun; Lin, Xiaoliang; Hong, Jiaxu; Liu, Kuai; Qi, Hui; Wang, Chaoying; Zhou, Yulin; et al. (Respiratory research, 2020)
Particulate Matter (PM) is known to cause inflammatory responses in human. Although prior studies verified the immunogenicity of PM in cell lines and animal models, the effectors of PM exposure in the respiratory system and the regulators of the immunogenicity of PM is not fully elucidated. To identify the potential effector of PM exposure in human respiratory system and to better understand the biology of the immunogenicity of PM, We performed gene-expression profiling of peripheral blood mononuclear cells from 171 heathy subjects in northern China to identify co-expressed gene modules associated with PM exposure. We inferred transcription factors regulating the co-expression and validated the association to T-cell differentiation in both primary T-cells and mice treated with PM. We report two transcription factors, IRF4 and STAT3, as regulators of the gene expression in response to PM exposure in human. We confirmed that the activation of IRF4 and STAT3 by PM is strongly associated with imbalanced differentiation of T-cells in the respiratory tracts in a time-sensitive manner in mouse. We also verified the consequential inflammatory responses of the PM exposure. Moreover, we show that the protein levels of phosphorylated IRF4 and STAT3 increase with PM exposure. Our study suggests the regulatory activities of IRF4 and STAT3 are associated with the Th17-mediated inflammatory responses to PM exposure in the respiratory tracts, which informs the biological background of the immunogenicity of particulate matters.